How to Win Schumpeterian Competition: Technological Transfers in the German Plastics Industry from the 1930s to the 1970s - Jochen Streb (Yale University, Economic Growth Center, 1999)
Introducing the concept of innovation capital we will analyse conditions under which a national industry is able to succeed in international Schumpeterian competition. Then we will discuss the significance of this concept for the economic development of the German plastics industry from the 1930s to the 1970s. Using a repeated game model of technological cooperation we will especially focus on technological transfers from chemical firms to plastics fabricators. We will deploy both a microeconomic approach when viewing product innovations transferred by the so-called Kunststoffrohstoffabteilung (KURO) of chemical firm BASF, and a macroeconomic approach when looking at the development of total factor productivity in the German plastics fabricating industry. It will turn out that we can distinguish three subperiods with respect to technological cooperation in the German plastics industry: the beginning in the period of National Socialist dictatorship and post war reconstruction, the developing in the time of the West German economic miracle, and the ending in the decade of the two oil price shocks.
Keywords: D83; L65; N64; O31; 330; Technological transfer; Schumpeterian competition; Repeated game; Plastics industry; Germany; Unternehmenskooperation; Technologietransfer; Chemieindustrie; Kunststoffindustrie; Deutschland